Nonlinear magnetoelectric coupling in magnetostrictive-piezoelectric composites. (15th November 2021) - Lin, Chien-hong; Lin, Ying-Zhao
Highlights: We study nonlinear magnetoelectric coupled responses of magnetostrictive-piezoelectric composites with 1-3, 0-3 and 2-2 connectivities. We formulate two micromechanics models, simplified unit-cell and Mori-Tanaka, that retain the similar mathematical structures. We examine the effect of the connectivity and proportion on the overall magnetoelectric coupling. The effective magnetoelectric coupling shows significant nonlinearity when the composite is subjected to large driving fields. Abstract: Two micromechanical formulations are established for analysis of nonlinear magnetoelectric coupling in composite materials with 1-3, 0-3 and 2-2 connectivities. The studied two-phase composites are constructed by magnetostrictive and piezoelectric phases that exhibit significant material nonlinearity when each or all of them are subjected to large driving magnetic or electric fields. The simplified unit-cell model is first formulated followed by a reformulation of the Mori-Tanaka model so that a comparison can be made between two micromechanics models in terms of their mathematical structures and micromechanical predictions. In order to analyze the nonlinear composites, a secant linearization is employed for each constituent, concentration-factor tensors are introduced for bridging microscopic and macroscopic behaviors, and residual vectors are defined for quantitation of the errors resulted from the linearization process. Micromechanical simulations show that 1) magnetoelectric coupling can be modulated by the composite connectivity and constituent proportion, and 2) the field-dependent magnetoelectric responses leads to significant difference between linear and nonlinear predictions.